2019
DOI: 10.9770/jesi.2019.7.2(2)
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable agriculture in Russia: research on the dynamics of innovation activity and labor productivity

Abstract: The article examines the dependence of the growth rates of labor productivity on the growth rates of investments in fixed assets in Russian agriculture. The approach used in this work to assess the intensity of innovation activity in agriculture is based on the ratio of investment efforts and the resulting dynamics of labor productivity. It is revealed that in the period from 2013 to 2017, the growth rates of investments in fixed assets significantly exceeded the growth rates of productivity in the industry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In terms of discussing the impact of environmental determinants on the performance of food producers and foodstuff trade, i.e., food availability and partial food access, Morkūnas, Volkov, and Pazienza [14], Morkūnas et al [15], and Tomchuk et al [16] mentioned that economic and environmental factors have an impact for resilience of agricultural enterprises. Similarly, Handayani, Wahyudi, and Suharnomo [17], Mikhaylova et al [18], Akhtar [19], Kheyfets and Chernova [20], Stjepanović, Tomić, and Škare [21], Cismas et al [22], Jayasundera [23], and Harold [24] proved that green innovations positively influence business performance, sustainability of agriculture, and food security. Haninun, Lindrianasari, and Denziana [25] mentioned that environmental performance has an effect on financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of discussing the impact of environmental determinants on the performance of food producers and foodstuff trade, i.e., food availability and partial food access, Morkūnas, Volkov, and Pazienza [14], Morkūnas et al [15], and Tomchuk et al [16] mentioned that economic and environmental factors have an impact for resilience of agricultural enterprises. Similarly, Handayani, Wahyudi, and Suharnomo [17], Mikhaylova et al [18], Akhtar [19], Kheyfets and Chernova [20], Stjepanović, Tomić, and Škare [21], Cismas et al [22], Jayasundera [23], and Harold [24] proved that green innovations positively influence business performance, sustainability of agriculture, and food security. Haninun, Lindrianasari, and Denziana [25] mentioned that environmental performance has an effect on financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Russia, researchers' interest in forming a digital economic space has grown significantly lately (Piskun et al, 2019). According to scientists Kheyfets and Chernova (2019), Gray and Rumpe (2017), Viollaz (2019), Stolterman and Croon (2004), Matt et al (2015), this is especially shown in revealing the relationship between the results of the application of information technologies by the business sector and the resulting performance indicators of the constituent entities of the Russian Federation -regions and municipalities (Matt et al, 2015). A new type of economy should be based on electronic resources that allow to process and revise large amounts of data (Popov & Semyachkov, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting approach [3], for assessing the intensity of innovation in agriculture, based on the ratio of investment efforts and the associated dynamics of labour productivity. Researchers [4] have identified some of the key factors affecting investment processes in mechanical engineering (labour force qualifications, production volume, dynamics of demand for the industry's products, the level of innovation activity within the industry, etc.).…”
Section: Literature Reviewmentioning
confidence: 99%